2018
DOI: 10.1111/gbi.12315
|View full text |Cite
|
Sign up to set email alerts
|

The Sirius Passet Lagerstätte of North Greenland—A geochemical window on early Cambrian low‐oxygen environments and ecosystems

Abstract: The early Cambrian Sirius Passet fauna of northernmost Greenland (Cambrian Series 2, Stage 3) contains exceptionally preserved soft tissues that provide an important window to early animal evolution, while the surrounding sediment holds critical data on the palaeodepositional water‐column chemistry. The present study combines palaeontological data with a multiproxy geochemical approach based on samples collected in situ at high stratigraphic resolution from Sirius Passet. After careful consideration of chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Overall, these data point toward 'suboxic' to anoxic (but non-sulfidic) conditions during deposition of the Chengjiang BST deposits. Echoing these results, a detailed multi-proxy study of the Series 2 Sirius Passet deposit in North Greenland reported transiently anoxic (ferruginous) conditions during the interval of highest soft-bodied fossil abundance and diversity [45].…”
Section: Redox Studies Of Bst Depositsmentioning
confidence: 79%
“…Overall, these data point toward 'suboxic' to anoxic (but non-sulfidic) conditions during deposition of the Chengjiang BST deposits. Echoing these results, a detailed multi-proxy study of the Series 2 Sirius Passet deposit in North Greenland reported transiently anoxic (ferruginous) conditions during the interval of highest soft-bodied fossil abundance and diversity [45].…”
Section: Redox Studies Of Bst Depositsmentioning
confidence: 79%
“…The highest diversity of animal species recorded in the interval between 3.0 and 7.7 m in the Sirius Passet succession corresponds to an interval where the water column appears to have contained very low concentrations of dissolved oxygen (Fig. 10); there is a significant positive correlation (P = 5.3 × 10 −7 ) between diversity and Fe HR /Fe T values (Hammarlund et al 2019). The intervals of low-oxygen water-column conditions thus directly correlate with preserved biodiversity.…”
Section: Box 2 Composition and Ecology Of The Faunamentioning
confidence: 97%
“…Although optimal conditions for preservation were associated with fluctuations in water-column chemistry and sea-level, we envisage that a substantial component of the Sirius Passet animal community also lived at or near the site, tolerating conditions of low watercolumn oxygen concentrations. The geochemical analysis indicates that the Sirius Passet Lagerstätte represents an early Cambrian biota that, in terms of oxygen, lived at concentrations that we today consider extremely low (Hammarlund et al 2019).…”
Section: Box 2 Composition and Ecology Of The Faunamentioning
confidence: 97%
See 2 more Smart Citations